Analysis of Local Content Policy Implementation in Company NJH - Daniel Simanjuntak; Adirizal Nizar (IPTEK Journal of Proceedings Series, 2021)
This study focused on 3 aspects of a virtual learning program on self-compassion: (1) changes in attitude and behavior at 3 time points: course initiation, course completion, and 6 weeks postcompletion, (2) differences between 2 formats: individual learning versus community learning, and (3) impact of 6 self-help tools. Eighty-eight randomly assigned participants were assigned to either an individual-learning group (ILG) or a community-learning group (CLG). Identical course information and materials were used in both groups; the difference was that the individual group privately watched the weekly video and had access to online interaction with each other, while the CLG watched the weekly video collectively on zoom followed by a live small-group interactive discussion. The results indicate that the course significantly improved attitude scores; the improvements occurred immediately at the completion of the course and were not temporary. Behavior scores also improved in both groups; however, participants within the CLG showed more behavioral improvement than participants in the ILG. Interestingly, the CLG rated the small-group interactive discussion as the most impactful tool, while the ILG rated the online interactive chat as the least impactful tool. These findings have relevance to both personal growth and well-being, as well as professional growth and employee wellness.